A Way to Improve Luminescent Efficiency of Bis-Chalcone Derivatives - Meng Guan, Tay; Mee Hing, Tiong; Ying, Ying Chia; Hui, Suzie Chin Kuan; Zhi-Qiang, Liu (Hindawi Publishing Corporation, 2016)
Chalcone related compounds have been reported as a poor luminescence molecule due to the quenching processes from the intramolecular torsional motions and cis-trans isomerization in the